Observations In Police Records And Their Prospection To Tutelas De Derecho In Criminal Proceedings - Hilter, Suarez Peña (South Eastern European Journal of Public Health, 2024)
The main objective of the research was to analyze the normative limits to establish party observations in police records as part of the exercise of the right to defense and its prospection to protect rights in criminal proceedings. The results of the investigation showed that Peru continues to suffer the effects of abusive police activity that generates irreparable damage to the human essence of the people intervened in an abusive manner or without respect for their fundamental rights because they develop within them a criterion of abusiveness and disproportionality in the treatment by the intervening police officers. For this reason, the investigation establishes the importance of the right to write the observations of the detainee or his defense in the police records in order to denounce on the spot the abuses or arbitrariness committed during the proceedings, since, in most cases, there is a nonsense in the exercise of the function and it is established that the detainee refused to sign the report. It was concluded that there are problems related to arbitrariness in the exercise of police functions that are not reported in a timely manner by the victims, generating mistrust against the authorities and public institutions.